Arthropod assemblages of the Quebrada del Morel private protected area (Atacama Region, Chile) - Pizarro Araya, Jaime (2012)
The objective of this baseline study was to use pitfall traps to examine the taxonomic composition and abundance of arthropods in the Quebrada del Morel private protected area located in the Atacama Region (Chile). The study area was divided into 10 vegetationally and pedologically contrasting sites: coastal steppe (CS), ravine bottom (RB), dunes with Prosopis flexuosa (PF), sandy-bottomed ravine (SBR), dunes with Skytanthus acutus (SA), coastal range (CR), piedmont with Nolana sp. (PN), inland dunes (ID), steppe with Nolana sp. (EN), and steppe with Atriplex sp. (EA). A total of 2187 specimens were captured, belonging to 73 species in 31 families. Of these 73 species, 26 belonged to Arachnida, and 47 to Insecta. The two dominant orders of the Arachnida assemblage were Solifugae (22.8% of total capture) and Araneae (5.7%). Insecta accounted for 69.1% of the total capture and was dominated by two orders: Coleoptera (33.8%) and Orthoptera (21.9%). The most abundant arthropod families were the solifuge Mummucidae (22.5%), the coleopteran Tenebrionidae (19.4%), and the orthopteran Gryllidae (18.8%). Particularly important among these families was Tenebrionidae which was represented by 18 species and 11 genera. The sites with the highest abundance of tenebrionids were PF (61.9%) and SBR (11.8%). The highest species diversity was observed in SBR (13) and PF (11). The differences in vegetation between the sites were clearly reflected in the numerical contribution of most taxa. This information will help implement compensation actions, develop a reclamation plan, and consolidate a conservation management plan for the Quebrada del Morel private protected area.